Respuesta :

Answer:

Please check the attached graph.

From the graph, it is clear that option B is the correct option.

Step-by-step explanation:

Given the function

[tex]g\left(x\right)=\:\frac{3}{2}\:\left(\frac{2}{3}\right)^x[/tex]

Determining the y-intercept

We know that the value of the y-intercept can be determined by setting x = 0, and determining the corresponding value of y.

so

substituting x = 0 in the fuction

[tex]y=\:\frac{3}{2}\:\left(\frac{2}{3}\right)^x[/tex]

[tex]y=\:\frac{3}{2}\:\left(\frac{2}{3}\right)^0[/tex]

Apply rule:  [tex]a^0=1,\:a\ne \:0[/tex]

[tex]y=1\cdot \frac{3}{2}[/tex]

[tex]y=\frac{3}{2}[/tex]

[tex]y = 1.5[/tex]

Therefore, the point representing the y-intercept is:

  • (0, 1.5)

Determining the x-intercept

We know that the value of the x-intercept can be determined by setting y = 0, and determining the corresponding value of x.

so

substituting y = 0 in the function

[tex]0=\frac{3}{2}\left(\frac{2}{3}\right)^x[/tex]

Using the zero factor principle

if ab=0, then a=0 or b=0 (or both a=0 and b=0)

[tex]\left(\frac{2}{3}\right)^x=0[/tex]

We know that [tex]a^{f\left(x\right)}[/tex] can not be zero or negative for x ∈ R

Thus, NONE represents the x-intercept.

Please check the attached graph.

From the graph, it is clear that option B is the correct option.

Ver imagen absor201
ACCESS MORE